A suggested framework and guidelines for learning GIS in interdisciplinary research. Issue 2 (11th December 2017) - Rickles, Patrick; Ellul, Claire; Haklay, Muki
Abstract : Interdisciplinary research with geographic information systems (GIS) can be rewarding as researchers from different disciplines have the opportunity to create something novel. GIS, though, is known to be difficult to use and learn. It is imperative for its successful use in projects that those who need to use GIS are able to learn it quickly and easily. To better support interdisciplinary research with GIS, it is necessary to understand what researchers with interdisciplinary experience wanted to use it for and how they learned it. The aim would be to advise geography educators on creating learning resources that could compliment or supplement existing learning approaches used by interdisciplinary researchers to improve the learning experience and uptake of GIS. This article explores the results from an online survey and interviews conducted between July 2014 and August 2015 with participants from the UK, the US and Europe on how interdisciplinary researchers learned GIS and which resources and platforms were utilised. Guidelines and a framework are presented, modifying the Technological Pedagogical and Content Knowledge framework, incorporating informal and context‐based learning and GIS concepts from the Geographic Information Science and Technology Body of Knowledge. Findings show that interdisciplinary researchers want to use GIS to capture, analyse and visualise information; they largely use informal learning approaches (e.g. internet searches, watching a video, ask a more experienced person); and they predominantly use ArcGIS, QGIS and web GIS platforms. Future work suggests resources use contextually relevant learning activities and bear in mind nuances of disciplinary language. Abstract : Geography is quite complimentary to interdisciplinary research as is one of its most powerful tools ‐ geographic information systems (GIS); however, such systems are known to be difficult to use. To better support interdisciplinary research initiatives that use GIS, it is first necessary to understand how those involved in previous similar projects have gone about learning GIS. Based on those findings, the article outlines a framework and guidelines, reinforced by educational theory and GIS curriculum, on how to support interdisciplinary researchers when they are learning GIS. e00046